O que pensam as pessoas com deficiência sobre a inclusão no setor bancário brasileiro: um estudo qualitativo - Tessima, Rose Mari (2018)
People with disabilities use banking services, however, in the empirical literature little evidence has been found linking the issue of the Person with disability and the accessibility with the offer of banking services. To characterize the theme, a literature review was carried out which emphasized: the technical standards. The legislation on Inclusion of Persons with Disabilities in the various segments of society. Their rights and obligations. The technological development that provides greater independence to the Person with Disabilities. Assistive technologies. Credit lines provided by banks for the acquisition of equipment, orthoses, prostheses and financing of architectural projects for residential accessibility. Banking applications for the segments of the Person with Disabilities. In this review it was found that there is a good evolution in the development of assistive technologies that seek to offer a better quality of life for the People with Disabilities. Brazil has good legislation regarding the rights and obligations of the Person with Disabilities, but there is still a way to be followed so that this legislation is understood, respected and fulfilled by Brazilian society, but this is a matter of cultural evolution that still lacks some time to consolidate. It was also found that there is a line of credit available to People with Disabilities, but it does not serve the entire population of people with disabilities. Banks are using technologies to provide care for this audience, such as screen reader, biometrics for customer identification, extracts in braille. Participants in the survey were People with Disabilities, with disabilities: physical, visual and auditory, who are clients of banks, not having been a profile of persons with associated disabilities. Having ascertained with the interviewees that they see their relationship with banks and banking products as "normal", not characterizing as good or bad, but very similar to what any ordinary citizen receives from banks, that many of his observations are common to other customers.